Racism and borders : representation, repression, resistance - Shantz, Jeff (Algora Pub., 2010)
Despite claims about globalization, we see increasing surveillance, tightened restrictions and growing punitive regimes at international borders. This critical collection examines processes of racialization in relation to border regulations and restrictions. It analyses border controls, racism, and representations of race, within multinational contexts as aspects of neo-liberal governance. It also looks at means by which people resist or challenge racialization. This collection uses the lenses of sociology, criminology, art, literary criticism and political science to critically examine varied.